Paddy-upland rotation improves soil quality by reshaping soil nematode and microbial communities - Pan, Sufeng; Wu, Yonghan; Chen, Jinzhi; Wang, Siliang; Cai, Xinyi; Wu, Pengfei; Wang, Xiaoe; Yan, Chengjin; Zheng, Yongli (Frontiers in Sustainable Food Systems, 2025)
Paddy–upland rotation systems are widely adopted to mitigate soil degradation in rice-based agroecosystems; however, their impacts on soil biota remain insufficiently understood. This study investigated the impacts of paddy continuous cropping (PA), upland continuous cropping (UP), and rice–loofah paddy–upland rotation (RO) on soil nematodes and microbial communities in southeastern China. Soil samples were collected prior to harvest at the end of the rice season and were analyzed for physicochemical properties, nematode communities via morphological identification, and microbial communities through high-throughput sequencing. The results showed that the RO system significantly increased soil pH, total phosphorus, available potassium, and available phosphorus, while reducing the abundance of the plant-parasitic nematode Hirschmanniella compared to the PA system. The total nematode abundance was highest in the UP system, where bacterivores predominated; the RO system was characterized by a higher proportion of algivores associated with flooded conditions, whereas the PA system was dominated by herbivores. The RO and PA system also improved nematode food web stability under flooded conditions, as indicated by higher maturity and structure indices relative to the UP system. Although microbial diversity did not differ significantly between systems, the community composition and predicted functional groups varied considerably. The relative abundance of Gemmatimonadota was significantly reduced in the PA system, while the abundance of Nitrospirota, Myxococcota, and Entorrhizomycota increased. Functional prediction revealed system-specific enrichment of bacterial metabolic groups associated with nitrogen cycling, carbon turnover, and redox-sensitive energy metabolism. Integration of soil physicochemical and biological indicators into a Soil Quality Index (SQI) ranked RO highest, underscoring its capacity to enhance soil ecological function and sustainability in rice-based systems.